Struktur Komunitas Padang Lamun Di Pulau Gurabosa Kecamatan Jailolo Selatan Kabupaten Halmahera Barat - Juniartin, Juniartin; Muna, Lintal; Umagap, Wirda Az. (IAIN Ternate, 2023)
Seagrass beds are one of the ecosystems that play an important role in marine life. This study aims to determine the type and community structure of seagrass beds based on the species diversity index, dominance index, and seagrass evenness index in the waters of Gurabosa Island, West Halmahera Regency. The research method uses the quadrant transect method with a size of 0.5 x 0.5 m. The results showed that the composition of the seagrass found consisted of 5 species of seagrass namely Enhalus acoroides, Halophyla ovalis, Thalassia hempricii, Cymodocea rotundata, Syringodim isoetifolium. The species diversity index (H') is included in the low species diversity criteria because the value of H' ˂ 1. The dominance index is also included in the low dominance criteria or no seagrass species dominate between stations. The evenness index of seagrass in the waters of Gurabosa Island is included in the low criteria. The low value of the evenness index of seagrass at the three stations is caused by the low index of seagrass diversity.Keywords: seagrass, community structure, diversity index, Gurabosa island.